Analysis of the Abasic Sites in Breast Cancer Patients With 5 Year Postoperative Treatment Without Recurrence in Taiwan - Che Lin MD-PhD; Chi-Yen Feng MD; Gilang P. Bahari MS; Sheng-Min Huang PhD; Cheng-Hao Wei MS; Qi Xu MS; Dat Thanh Dinh PhD; Dar-Ren Chen MD; Po-Hsiung Lin PhD (Cancer Control)
Purpose This prospective study aimed to investigate estrogen-induced carcinogenesis by assessing the background levels of abasic sites (apurinic/apyrimidinic sites, AP sites) in Taiwanese breast cancer patients following 5 years of postoperative treatment without recurrence (5-year survivors) (n = 70). The study also sought to compare the extent of these DNA lesions with those found in healthy controls and in breast cancer patients prior to treatment. Methods Abasic sites were measured using an aldehyde reactive probe and quantified as the total number of abasic sites per total nucleotides. Characterization of the abasic sites in subjects recruited for this study was conducted using the abasic site cleavage assay using putrescine or T7 exonuclease (T7 Exo) and/or exonuclease III (Exo III). Results The number of abasic sites detected in 5 year survivors (26.7 ± 10.2 per 10 6 total nucleotides, n = 70) was significantly reduced by 46.9% compared to those in breast cancer patients before treatment (50.3 ± 59.2 per 10 6 total nucleotides, P < 0.001), and was similar to the levels observed in healthy controls (23.3 ± 13.5 per 10 6 total nucleotides, P > 0.05). Further investigation into the specific types of abasic sites indicated that the number of abasic sites excisable by putrescine in controls, breast cancer patients, and 5-year survivors were 63.3%, 78.6%, and 67.7%, respectively. These findings suggest the involvement of oxidative stress rather than depurination/depyrimidination of DNA adducts in the formation of abasic sites. Further analyses were performed using exonuclease cleavage assay to characterize the specific types of abasic sites including 5′-cleaved, 3′-cleaved, intact, and residual abasic sites. Results demonstrated that the proportion of residual abasic sites detected in controls, breast cancer patients, and 5-year survivors were estimated to be 32.7%, 48.8%, and 34.0%, respectively. Conclusion Overall, these findings suggest clear evidence of treatment-related effects on the reduction of levels of abasic sites as well as on the profile of abasic sites in 5 year survivors.